Congress of Neurological Surgeons Systematic Review and Evidence‐Based Guidelines on the Role of Radiosurgery and Radiation Therapy in the Management of Patients With Vestibular Schwannomas. Issue 2 (February 2018) - Germano, Isabelle M; Sheehan, Jason; Parish, Johnathan; Atkins, Tyler; Asher, Anthony; Hadjipanayis, Constantinos G; Burri, Stuart H; Green, Sheryl; Olson, Jeffrey J
Abstract : RADIOSURGERY VS OBSERVATION : Question What are the indications for stereotactic radiosurgery (SRS) treatment vs observation for patients with intracanalicular vestibular schwannomas without evidence of radiographic progression? Recommendation Level 3: If tinnitus is not observed at presentation, it is recommended that intracanalicular vestibular schwannomas and small tumors (<2 cm) without tinnitus be observed as observation does not have a negative impact on tumor growth or hearing preservation compared to treatment. RADIOSURGERY TECHNOLOGY : Question Is there a difference in outcome based on radiosurgery equipment used: Gamma Knife (Elekta, Stockholm, Sweden) vs linear accelerator‐based radiosurgery vs proton beam? Recommendation There are no studies that compare 2 or all 3 modalities. Thus, recommendations on outcome based on modality cannot be made. RADIOSURGERY TECHNIQUE : Question Is there a difference in outcome based on the dose delivered? Recommendation Level 3: As there is no difference in radiographic control using different doses, it is recommended that for single fraction SRS doses, <13 Gy be used to facilitate hearing preservation and minimize new onset or worsening of preexisting cranial nerve deficits. Question Is there a difference in outcome based on the number of fractions? Recommendation As there is no difference in radiographic control and clinical outcome using single or multiple fractions, no recommendations can be given. RADIOGRAPHIC FOLLOW‐UP, RETREATMENT, AND TUMORIGENESIS AFTER RADIOSURGERY : Question What is the best time sequence for follow‐up images after SRS? Recommendation Level 3: Follow‐up imaging should be obtained at intervals after SRS based on clinical indications, a patient's personal circumstances, or institutional protocols. Long‐term follow‐up with serial magnetic resonance imagings to evaluate for recurrence is recommended. No recommendations can be given regarding the interval of these studies. Question Is there a role for retreatment? Recommendation Level 3: When there has been progression of tumor after SRS, SRS can be safely and effectively performed as a retreatment. Question What is the risk of radiation‐induced malignant transformation of vestibular schwannomas treated with SRS? Recommendation Level 3: Patients should be informed that there is minimal risk of malignant transformation of vestibular schwannomas after SRS. NEUROFIBROMATOSIS TYPE 2 : Question What are the indications for SRS in patients with neurofibromatosis type 2? Recommendation Level 3: Radiosurgery is a treatment option for patients with neurofibromatosis type 2 whose vestibular schwannomas are enlarging and/or causing hearing loss. The full guideline can be found at:https://www.cns.org/guidelines/guidelines‐management‐patients‐vestibular‐schwannoma/chapter_7 .